Developing interactive pedagogies: A case of accounting pre-service teachers from Ghana - Bernard Fentim Darkwa; Douglas Darko Agyei; Joseph Tufuor Kwarteng (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2024)
This is a study of how eight pre-service teachers developed their skills in developing interactive lessons to teach concepts in Accounting in Senior High Schools in Ghana. Sequential multiple case study design was employed to observe two cohorts of four pre-service teachers who worked in two phases of a professional development scenario to design and enact interactive Accounting lessons. Data for the study were collected through observation, interviews, lesson documents and questionnaires. Pictures, content and thematic analysis procedures were used to analyse the qualitative data, whilst means and standard deviation were used to analyse the quantitative data. It emerged from the results that the interactive lessons developed and implemented by the pre-service teachers were effective in promoting participation in the classroom.  The study also brought to light that interactive teaching promotes collaboration among students through solving problems in groups which helps to strengthen the bond between students. The study thus, advocates the need for teacher training institutions to focus on training teachers to acquire the skills in designing and enacting lessons interactively to promote students' participation in the classroom.